Green behavior and generation: A multi-group analysis using structural equation modeling - Bautista, Reynaldo A. (Animo Repository, 2019)
The purpose of this research is to investigate the difference between generations X and Y in terms of green behavior operationalized as an intention to buy green products (INT). The study was based on two cross-sectional samples—one for generation X (N=397) and one for generation Y (N=685). Model testing was conducted using structural equation modeling (PLS-SEM). At the overall model, results showed that all variables are significant (with p-values ≤ 0.05) predictors of INT. However, at the generation level, there is a significant difference in green values (GV) between generations where generation X registered a higher score. Furthermore, t-test of the path coefficients from GV to attitude toward green product (ATT), perceived behavioral control (PBC), and subjective norm (SN) are all statistically significant. The study suggests that marketers should consider a unique selling approach to each of the generations. For instance, as generation X has a higher score in GV, when targeting this group, marketing campaigns should highlight that their actions have a direct effect on the environment whether positive or negative. © 2019 by De La Salle University.